Comparison of clinical features of cystic fibrosis patients eligible but not on CFTR modulators to ineligible for CFTR modulators - Buyuksahin, Halime Nayir; Emiralioglu, Nagehan; Yalcin, Ebru; Sen, Velat; Sen, Hadice Selimoglu; Arslan, Huseyin; Dogru, Deniz (Wiley, 2024)
Introduction: Cystic fibrosis transmembrane conductance regulator (CFTR) modulator drugs target the underlying defect and improve CFTR function. They are a part of standard care in many countries, but not all patients are eligible for these drugs due to age and genotype. Here, we aimed to determine the characteristics of non-eligible patients for CFTR modulators in the CF registry of Turkey (CFRT) to highlight their clinical needs. Methods: This retrospective cohort study included CF patient data from the CFRT in 2021. The decision of eligibility for the CFTR modulator was determined according to the 'Vertex treatment-Finder' on the Vertex (R) website. Demographic and clinical characteristics of patients were compared between eligible (group 1) and ineligible (group 2) groups for CFTR modulators. Results: Among the study population (N = 1527), 873 (57.2%) were in group 1 and 654 (42.8%) were in group 2. There was no statistical difference between groups regarding sex, meconium ileus history, diagnoses via newborn screening, FEV1 z-score, CF-associated complications, organ transplant history, and death. Patients in group 2 had a higher incidence of pancreatic insufficiency (87.7% vs. 83.2%, p = .010), lower median height z-scores (-0.87 vs. -0.55, p < .001), lower median body mass index z-scores (-0.65 vs. -0.50, p < .001), longer days receiving antibiotics due to pulmonary exacerbation (0 [interquartile range, IQR: 0-2] vs. 0 [IQR: 0-7], p = 0.001), and more non-invasive ventilation support (2.6% vs. 0.9%, p = 0.008) than patients in group 1. Conclusion: The ineligible group had worse clinical outcomes than the eligible group. This highlights their need for life-changing drugs to improve clinical outcomes.
Keywords: CFTR modulators; clinical features; cystic fibrosis; eligibility; registry